Steady and Temporary Expressions of Smooth Muscle Actin in Hair, Vibrissa, Arrector Pili Muscle, and Other Hair Appendages of Developing Rats - Morioka, Kiyokazu (Japan Society of Histochemistry and Cytochemistry, 2011)
The hair erection muscle, arrector pili, is a kind of smooth muscle located in the mammalian dermis. The immunohistochemical study using an antibody against smooth muscle alpha actin (SMA) showed that the arrector pili muscle develops approximately 1–2 weeks after birth in dorsal and ventral skin, but thereafter they degenerate. The arrector pili muscle was not detected in the mystacial pad during any stage of development, even in the neighboring pelage-type hair follicle. A strong signal of SMA in the skin was located in the dermal sheath as well as in some outer root sheath cells in the hair and vibrissal follicles. Positive areas in the dermal and outer root sheaths were restricted to a lower moiety, particularly areas of similar height, where keratinization of the hair shaft occurs. This rule is valid for both pelage hair follicles and vibrissal follicles. At medium heights of the follicle, SMA staining in the dermal sheath was patchy and distant from the boundary between dermis and epidermis. In contrast to SMA, vimentin was expressed over the entire height of the dermal sheath. Unlike the arrector pili muscle, the expression of SMA in the dermal sheath was observed during fetal, neonatal, and adult stages. The presence of actin-myosin and vimentin fibers in supporting cells is thought to be beneficial for the hair follicle to cope with the movement of the hair shaft, which may be caused by physical contacts with outside materials or by the contraction of internal muscles.